[Criminal] : Local & Special Laws : Minor Acts : Central & Provincial : (Amendment Up-to-Date) : (With Short Notes) : Throughly Revised - Arif Ali Meer; Revised by Hassan Mehmood Butt (Lahore Khyber Law Publisher, 2012)
This book contains the minor acts and codes of crimes and justice which implimented in the all courts of Pakistan.
Includes End-Note of Pages.
Contents According to Alphabatical Order.
Keywords: Criminal Law -- Local & Special Laws -- Central & Provincial